DISCOURSE “PHILOSOPHY OF FINANCIAL ANALYSIS” IN THE STRUCTURE OF ECONOMIC KNOWLEDGE - ZHUKEVYCH, Svitlana (Scientific journal «World of Finance», 2025)
Introduction. Global challenges and a dynamic understanding of our changing world form a new paradigm, the foundation of which is in fundamental research and practical applications of scientific intelligence, which allows obtaining significant results and finding solutions to global and local problems. One of the forms of multidisciplinarity is the convergence and development of scientific knowledge – philosophy and economic sciences, including financial analysis. The peculiarities of the formation and development of financial analysis as an independent science require the study of its philosophical foundations. The purpose of the article is to study the theoretical aspects of the philosophy of financial analysis and its place in the structure of economic knowledge in order to solve the hermeneutic issues of creating an effective model of financial analysis as a holistic science. Results. It is outlined that the philosophy of the economic world determines general, universal trends and patterns of its development based on philosophical categories: goals, explanations, theories, verification, induction and demarcation. The expansion of the subject field of the philosophy of economics made it possible to single out the philosophy of financial analysis. It has been proven that the existence of financial analysis as a separate, independent, holistic science is a reason to investigate its philosophical foundations, and the discourse “philosophy of financial analysis” covers philosophical questions of the “nature” and structure of scientific explanation, justification of the scientific method, changes in scientific theory, the status of scientific laws, the discussion between scientific-realist and anti-realist approaches and occupies considerable importance in the system of economic sciences. Conclusions. Therefore, the formation of the philosophical foundations of the scientific economic system, the provision of reliable and substantive knowledge about financial analysis, substantiated in a thorough (comprehensive) logical theoretical form, is the need of today. After all, the philosophy of financial analysis studies philosophical questions of the “nature” and structure of scientific explanation, the justification of methods, changes in scientific theory, the status of scientific laws, and the debate between scientific-realist and anti-realist approaches. The understanding of the philosophy of financial analysis as a discipline is revealed through the interrelated components, philosophical dimensions of financial analysis: ontological, epistemological, epistemological, axiological, methodological, which influence and determine the research paradigm and will be the subject of further scientific investigations, as they form the philosophical doctrine of financial and economic reality.